Identifikasi Kandungan Senyawa Metabolit Sekunder dan Uji Bioaktivitas Terhadap Larva Udang (Artemia salina Leach.) Ekstrak Daun Kecapi (Sandoricum koetjape Merr.) - Destri Erawaty; Aditya Fridayanti; Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2016)
Secondary metabolites identification and bioactivity of santol leaves extract (S.koetjape Merr.) against Artemia salina Leach has been done. Secondary metabolite identification was done by testing santol leaves extract and fractions against reagent, whereas the bioactivity tests carried out by Brine Shrimp Lethality Test (BSLT) method. Santol leaves extract was extracted using methanol solvent and was fractioned using n-hexane, ethyl acetate and n-butanol solvents. The results showed that the santol leaves extract contain flavanoid, saponin, tannin, karatenoid, fenol, steroid, and triterpenoid. LC50 value of each crude extract, n-hexane fraction, ethyl acetate fraction, and n-butanol fraction was 190.12 ppm, 189.23 ppm, 299.23 ppm, and 301.99 ppm.